PENGEMBANGAN MEDIA POP UP BOOK BERBASIS KEARIFAN LOKAL PADA MATERI PENINGGALAN SEJARAH KELAS IV SD NEGERI SUKOWUWUH - Naili Ulya; Titi Anjarini; Nurhidayati (STKIP Subang, 2024)
This study aims to: 1) Develop a Learning Media Product in the form of a Pop-Up Book Based on Local Wisdom for Historical Heritage Material in Fourth Grade of Elementary School, following the research and development procedures. 2) Determine the feasibility of the Pop-Up Book Learning Media Based on Local Wisdom for Historical Heritage Material in Fourth Grade of Elementary School. The type of research used in this study is research and development (R&D). The research model uses ADDIE, which consists of 5 development stages. The research subjects are 15 fourth-grade students of SD Negeri Sukowuwuh in the 2023/2024 academic year. Data collection techniques include observation, interviews, and questionnaires. The data collection instruments consist of observation sheets, interviews, validation questionnaires from media experts, material experts, teacher responses, and student responses. The data analysis techniques used include feasibility analysis, practicality analysis, and effectiveness analysis. The results of the development of the Pop-Up Book Media are: 1) The research produced a Learning Media Product in the form of a Pop-Up Book Based on Local Wisdom for Historical Heritage Material in Fourth Grade of Elementary School. 2) The product feasibility achieved an average score of 82.5%, which falls into the